Killing the killers [large type] : the secret war against terrorists - O'Reilly, Bill; Dugard, Martin (O'Reilly, Bill. Killing series, 2022)
"As the World Trade Center buildings collapsed, the Pentagon burned, and a small group of passengers fought desperately to stop a third plane from completing its deadly flight plan, America went on war footing. Killing The Killers narrates America's intense global war against extremists who planned and executed not only the 9/11 attacks, but hundreds of others in America and around the world, and who eventually destroyed entire nations in their relentless quest for power"--